A (in)suficiência do paradigma dogmático no modo de observar e ensinar o direito - Costa, Bárbara Silva (Universidade do Vale do Rio do Sinos, 2007)
To study the (in) adequacy from law dogmatic in the way to observe and teach law necessarily implies in knowing the context of its appearance. The way of how is wanted to perform this activity comes from the scientific perception developed for Descartes and Newton in XVI and XVII centuries. The quest for a correct, safe, pure and true knowledge also can be found in law study. The dogmatic, considered scientific paradigm from dominant law in modernity continues influencing today the Brazilian law and educational structures. The mechanics models and the law thinking are limited in front of the complexities, disorders, uncertainties and insecurities of the world. However, it remains recurrent in imagination of jurists who present reducing, minimalist, excluding and insufficient conceptions from law study and society. Observing this, it’s possible to talk in a paradigm crisis which demands a new way to see the world considering the risks and existing paradoxes. The institution of law knowledge in Brazil had innum
Keywords: cursos de direito; Instituições de Ensino Superior; mudança epistemológica; paradigma dogmático; teoria dos sistemas; ensino jurídico; mecanicismo; Colleges; epistemological change; law courses; law study; paradigm dogmatic; systems theory; mechanics; Ciências Sociais Aplicadas